TECHNICAL AND PRODUCTIVITY MANAGEMENT STUDY OF CRUSHING PLANT TO ACHIEVE THE TARGET OF SPLIT STONE PRODUCTION IN ROCK MINING COMPANIES IN WEST KALIMANTAN - Syahrudin, Syahrudin; Michelim, Stanley; Nuh, Safarudin M (Fakultas Teknik Universitas Tanjungpura, 2023)
West Kalimantan has adequate and economically valuable rock reserves to be developed as a primary material for construction through rock-crushing activities using a rock crusher. Currently, in West Kalimantan, several mining companies produce rock, namely PT. Bukit Labu Mining and PT. Sulenco Wibawa Perkasa produces andesite, PT. Total Optima Prakarsa produces granodiorite, and PT Hasindo Mineral Persada produces granite. In general, production targets have not been achieved. This study aims to conduct technical and management studies on crushing plant productivity and the factors that cause the company's production target not to be achieved and to make efforts to increase productivity so that production targets can be met. Based on the research results, it is known that the factors causing the production target not to be achieved the technical aspects of the equipment and the management factors of the operational production management, which have not been optimal. Increasing the technical capability of the tool is carried out by increasing the amount of incoming feed by optimizing work compatibility between the dump truck and the crusher, reducing the material entering the crusher's size, increasing the crusher's setting, and increasing the workability of the tool.